Diversidad florística y factores asociados a la abundancia de la regeneración natural del bosque montano del parque universitario “Francisco Vivar Castro”, Loja, Ecuador - Armijos Labanda, César Fernando (2021)
The floristic diversity and the factors associated with the abundance of natural regeneration is important to know to plan the management of the floristic resources of the forest. The objective of the research was to determine the natural regeneration and the factors associated with the abundance of the montane forest of the “Francisco Vivar Castro” University Park. For the evaluation of the floristic composition, structure and diversity of natural regeneration, 24 temporary plots of 20 x 20 m were installed in which the high pole stage was recorded, in a nested manner 3 subplots of 5 x 5 m were installed to describe low pole stage and 5 subplots of 2 x 2 m for the description of the seedlings, all the plots were randomly located in representative areas of the montane forest. The association of the abundance of natural regeneration with variables such as canopy cover, slope of the terrain and depth of organic soil, was made by applying the Pearson correlation coefficient and the Determination coefficient. The natural regeneration of 3893 individuals belonging to 55 species, 43 genera and 30 families was registered, being 12 tree species, 41 shrub species and 2 herbaceous ones; The highest amount of natural regeneration presents the low pole stage category with 1790 individuals (45.98%), followed by the sapling category with 1549 individuals (39.79%) and the high pole stage category with 554 individuals (14.23%). The most ecologically important species (IVI) are: Palicourea amethystina, Clusia latipes, Miconia obscura, Piper andreanum, Myrsine sodiruana, Vinurnum triphyllum and Prunus opaca. The specific diversity of natural regeneration according to the Shannon index is 3.17 considered as "medium" and 0.94 according to Simpson, which represents a "high" fairness. The physical variables that have the greatest influence are: canopy coverage that acts directly with a moderate intensity on the low and high pole stages, the correlation being statistically significant; the slope of the terrain is manifested in such a way that as the slope increases the abundance decreases in the three categories studied; On the other hand, the depth of the organic soil shows a weak correlation with the low pole stages, and no type of relationship with the sapling and high pole stage categories. The analysis of main components and correlation allowed to determine that the vegetation cover is the most determining variable in terms of factors for the establishment of individuals that allow to ensure natural regeneration processes. Keywords: Natural regeneration, Montane forest, Specific diversity, Physical variables, Correlation.